Antemortem diagnosis of congenital glaucoma in a white‐bellied caique (Pionites leucogaster). (2nd September 2020) - Cococcetta, Ciro; Collarile, Tommaso; Masi, Marco; Giudice, Chiara; Selleri, Paolo; Huynh, Minh
Abstract: A 34‐day‐old, male, white‐bellied caique ( Pionites leucogaster ) was presented for a complaint of bilateral buphthalmos. Clinical examination was unremarkable apart from the ophthalmic findings. The ophthalmologic examination was negative for direct, consensual, and dazzle reflexes in both eyes. The intraocular pressure exceeded 40 mm Hg OU. Fluorescein stain demonstrated corneal surface lesions suggestive of exposure keratopathy subsequent to bilateral buphthalmos. Diagnostic imaging tests were conducted to perform ocular biometric measurements and investigate the intraocular structures, including the iridocorneal angle and lens, by means of high‐resolution ultrasonography (HRUS). The presence of congenital glaucoma in this young parrot was strongly suspected after clinical and ophthalmological examination and the results of diagnostic imaging. Pharmacological treatment to reduce intraocular pressure was initiated using dorzolamide hydrochloride 2% and timolol maleate 0.5%. A month later, the parrot's eyes did not show any visual improvement, but the intraocular pressure had returned to normal. The parrot was unable to feed itself and died during a feeding procedure. Postmortem examination revealed ab ingestis pneumonia. Both eyes were submitted for histopathology, with severe anterior segment dysplasia and goniodysgenesis found OU. Histological findings added to the clinical presentation, the ophthalmologic examination and the imaging findings, confirmed the presence of congenital glaucoma.